Economization of production of the mill bar and rolled wire - S. M. Zhuchkov (Литьë и металлургия)
There are examined the main directions of investigations\ in the field of the theory and technology of continuous rolling of the rolled section and rolled wire. There is shown, that investigations and development works are directed at solution of actual problems in the field of the section rolling production — economization of its production, providing competitiveness of rolled metal in the home and foreign market due to reduction of energy and material costs.